Paper-based microfluidic fuel cells and their applications: A prospective review. (15th July 2022) - Tanveer, Muhammad; Ambreen, Tehmina; Khan, Haroon; Man Kim, Gyu; Woo Park, Cheol
Graphical abstract: Highlights: A methodical approach for understanding the paper-based microfluidic fuel cells. Fabrication strategies of various paper-based microfluidic fuel cell has been reviewed. Paper-based microfluidic fuel cells with different types of fuels are summarized and compared. Stacking efficiency is compared among different paper-based microfluidic fuel cell stacks. Applications, challenges and prospects have been discussed. Abstract: Since they firstly appeared in 2014, paper-based microfluidic fuel cells (PMFC) have received great attention in the past few years, mainly being used for sensors, wearable devices, point-of-care testing and diagnostics. This fuel cell technology exploits the intrinsic characteristics of paper substrate and microfluidic flows of reactant streams eliminating the need for external pumps and conventional membranes. PMFCs operate in a co-laminar flow configuration, and the absence of convective mixing across the liquid–liquid interface of two streams forms a distinct diffusive mixing region, which acts as a pseudo–membrane. The hydrophilicity and porosity of paper substrate allows reactants to flow by capillarity with the assistance of an absorbent pad. Ions can be transported across the channel through the mixing region to reach the other side of the channel and complete ionic conduction. To date, several fuels have been utilised in PMFCs, such as formate, hydrogen, formic acid, hydrogen peroxide, hydrocarbons, borohydride, hydrazine, and biofuels, each of which has specific advantages and disadvantages. This review article summarises the growth of PMFC technology, from its invention in 2014 until the present, with emphasis on fundamentals, fabrication methods, unit cell performance with various fuels, performance achievements, design considerations, and scale-up options. The applications and main challenges associated with the current status of the technology are provided along with future perspectives. Investigations in recent years have shown that PMFCs developed with different fuels enhance power density from several µWcm −2 to several mWcm −2 and that stacking multiple individual cells increases the working voltage. Moreover, enzymatic and microbial PMFCs show great potential to be used as wearable devices, sensors and in lab-on-chip devices.